Pengaruh ESG Disclosure dan Sales Growth terhadap Return Saham: Peran Moderasi Ukuran Perusahaan - Supri Yanto; Putri Irmala Sari (Wahana Riset Akuntansi, 2026)
Abstract Purpose – This research investigates how Environmental, Social, and Governance disclosures and sales expansion affect stock returns, and additionally, it scrutinizes the moderating effect of company size on these connections within Indonesia's capital market.   Design/methodology/approach – This study employs a quantitative methodology, specifically using moderated panel regression analysis. The research sample comprises non-financial corporations continuously listed on the Indonesia Stock Exchange between 2023 and 2025, which were chosen through purposive sampling. ESG disclosure is quantified via content analysis following GRI Standards, sales growth is determined by the annual percentage change in net sales, and firm size is represented by the natural logarithm of total assets. The data analysis process includes classical assumption diagnostics, procedures for selecting the appropriate panel model, and moderated regression incorporating interaction terms.   Findings – Results from empirical investigations show a notable positive correlation between ESG disclosure and stock returns, thereby reinforcing its status as a credible signal that mitigates information asymmetry and strengthens investor confidence. Sales growth similarly demonstrates a significant positive impact, reflecting the market's valuation of fundamental operational expansion. Furthermore, firm size significantly strengthens both relationships, supporting the resource-based view that larger firms' greater visibility, credibility, and resource capacity amplify the market's reception of ESG and growth signals.   Originality/value – This research contributes by simultaneously integrating sustainability disclosure, operational performance, and structural characteristics within a unified moderated framework, addressing a significant gap in the emerging market literature. It provides novel empirical evidence on the conditional effects of ESG disclosure in Indonesia, highlighting the contextual importance of firm scale.   Research limitations/implications – The findings are constrained by the three-year observation period, the use of self-constructed ESG disclosure metrics, and the exclusion of the financial sector. Future studies should extend the timeframe, employ independent ESG ratings, and explore additional moderating variables such as governance quality or institutional ownership to deepen the understanding of these dynamics.